Offenses Against Public Safety, Chapter 6, § 420 - (:unkn) unknown (General Publisher, 1885)
Prohibited carrying concealed any brass knuckles, slung-shot, or other weapon of like kind, or carries a rifle, shot gun walking cane. Violators fined not exceeding one hundred dollars, and may be imprisoned, or put to hard labor not exceeding sixty days.
--
Keywords: CARRY